Determination of Flowing Electrolyte Parameters in a Zinc-Air Fuel Cell by the Taguchi Method. (10th April 2023) - Huang, K. David; Nguyen, Minh-Khoa; Yang, Cheng-Jung; Chen, Po-Tuan
Abstract : The flowing electrolyte in a zinc-air fuel cell (ZAFC) can reduce the problem of incomplete reaction caused by the concentration gradient of the electrolyte. In this study, we propose a self-developed ZAFC with a flowing electrolyte system and optimize control parameters. The anode of the ZAFC used Zn particles through which the electrolyte penetrates and combined with a negative pressure pump to allow the potassium hydroxide (KOH) electrolyte to have an effective chemical reaction with the Zn particles during the discharge process. However, the flow rate of the electrolyte is required to match other control parameters, such as operating temperature, KOH concentration, and cell size, to effectively improve the efficiency of ZAFC. Therefore, the Taguchi method is adopted to obtain the optimal reaction parameters and the key factors affecting the discharge efficiency of the cell. The best operation condition is the temperature at 50°C, the KOH concentration of 30% wt, and the electrolyte flow rate of 150ml/min; then, the maximum power obtained from the experimental results is 13.8 W, the maximum current density reaches 699.721  mA/cm 2, and the maximum power density is 395.037 mW/cm 2 . This paper provides valuable insights for the upgrade of ZAFC for future practical applications.